In vivo stabilization of OPA1 in hepatocytes potentiates mitochondrial respiration and gluconeogenesis in a prohibitin-dependent way - Li, Lingzi (J Biol Chem, 2019)
Patients with fatty liver diseases present altered mitochondrial morphology and impaired metabolic function. Mitochondrial dynamics and related cell function require the uncleaved form of the dynamin-like GTPase OPA1. Stabilization of OPA1 might then confer a protective mechanism against stress-induced tissue damages. To study the putative role of hepatic mitochondrial morphology in a sick liver, we expressed a cleavage-resistant long form of OPA1 (L-OPA1Δ) in the liver of a mouse model with mitochondrial liver dysfunction (i.e. the hepatocyte-specific prohibitin-2 knockout (Hep-Phb2(−/−)) mice). Liver prohibitin-2 deficiency caused excessive proteolytic cleavage of L-OPA1, mitochondrial fragmentation, and increased apoptosis. These molecular alterations were associated with lipid accumulation, abolished gluconeogenesis, and extensive liver damage. Such liver dysfunction was associated with severe hypoglycemia. In prohibitin-2 knockout mice, expression of L-OPA1Δ by in vivo adenovirus delivery restored the morphology but not the function of mitochondria in hepatocytes. In prohibitin-competent mice, elongation of liver mitochondria by expression of L-OPA1Δ resulted in excessive glucose production associated with increased mitochondrial respiration. In conclusion, mitochondrial dynamics participates in the control of hepatic glucose production.